Effect of EAP Psychological Intervention on Improving the Mental Health of Medical Workers Under the Novel Coronavirus Epidemic in China - Xu, Jun; Liu, Xia; Xiao, Yundan; Fang, Xiaohui; Cheng, Yingsheng; Zhang, Jinping (Frontiers in Public Health, 2021)
Objective: Due to the novel coronavirus epidemic, medical workers are under immense psychological pressure. As such, the East Campus of Shanghai Sixth People's Hospital actively adopted the Symptoms Checklist 90 (SCL-90) to evaluate the mental health of staff members at the hospital before and after a psychological intervention from the Employee Assistance Program (EAP). Methods: Medical workers from the East Campus of Shanghai Sixth People's Hospital were recruited for this study. Psychological evaluations were conducted using the SCL-90, with a score of > 160 regarded as a positive result, or in other words, an indication of abnormal psychological symptoms. The EAP adopted different forms of psychological interventions for healthcare professionals, and participating in these measures was completely voluntary. Medical workers completed the SCL-90 again after participating in a psychological intervention, and we analyzed the changes between their two assessments. Results: Of the 1,198 total medical staff present in the hospital, 844 participated in the initial survey while only 652 completed the survey a second time (i.e., post-psychological intervention). We found that employees with abnormal psychological symptoms (i.e., an SCL-90 score of > 160) tended to be female, nurses, between 30 and 39 years old, individuals with intermediate professional titles, and unmarried. Moreover, we found that where healthcare professionals work has a significant impact on their psychological well-being; the scores of medical staff working in Hubei, the fever clinic, and the Shanghai Public Health Center scored higher on the SCL-90 than healthcare professionals working elsewhere (p < 0.05). Following psychological intervention, we found that mental health of hospital workers improved, as indicated by their second SCL-90 evaluations, although the proportion of medical staff willing to participate in the second evaluation was lower than the initial assessment. Conclusion: Hospitals have the potential to alleviate and reduce the psychological pressure placed on medical staff members through the EAP, which can actively adopt intervention and guidance measures. The findings of this study have important implications, as reducing abnormal psychological symptoms of healthcare professionals can be helpful in the fight against the coronavirus epidemic.